The effects of atmosphere-ocean-wave coupling during tropical cyclone - Garg, Nikhil (Nanyang Technological University, 2018)
It is well recognized that air-sea interaction affects the development and modulation of tropical cyclone (TC). However, open questions remain as to how and to what extent air-sea interaction affects the structure and intensity of a TC. This research project investigates and provides a better understanding of the coupling of atmosphere, ocean and ocean wave systems at the interface (i.e. sea surface) and its impacts on the TC structure. It is intuitive to think that, at the earth's surface, the fluid (both air and water) layer belongs to a single system, thus, justifying the construction of a single dynamically coupled model where atmosphere and ocean are interacting on different temporal and spatial scales. Within this coupled system, it can be thought that the ocean waves generated at the sea surface are due to the momentum transfer from atmosphere, which subsequently gets transferred to ocean. This transfer of momentum (from atmosphere to ocean) is not a one-way link, i.e., there are feedback effects from ocean (both in terms of enthalpy and momentum) on the atmospheric boundary layer.